Protecting Oil Flowlines from Corrosion Using 5-ACETYL-2-ANILINO-4-DIMETHYLAMINOTHIAZOLE - Fatima Mahmood Shaker, Dhifaf Jaafar Sadeqb (Pakistan Journal of Medical & Health Sciences, 2022)
Oil flow lines are used to transport oil and its derivatives from a well over long distances, and because oil wells produce other potentially corrosive products, such as carbon dioxide and Hydrogen sulfide, it is necessary to take methods to protect the pipeline from corrosion. One of these methods is the use of corrosion inhibitors in this study. Prepare 5-acetyl-2-anilino-4-dimethylaminothiazole and test it as a corrosion inhibitor on a sample of the Rumaila flow line at a constant temperature 25°C in (3.5%) NaCl and (3.5%) KCl solution in the absence and presence of different concentrations of inhibitor (0 mM, 0.01 mM, 0.03 M, 0.05 mM). by using liner polarization (Tafel slope). The inhibiter exhibited the best performance at high concentration giving 94% in NaCl solution and 88% in KCl solution and solution, the inhibitor gave It was used FT-IR to find out the effective aggregates in the inhibitor, Tafel plot reveals that Ecorr for flowline in the presence the inhibitors shift to a higher (noble) position compared with blank solution, implying that the protection acts as an anodic protection. Keywords: corrosion inhibiter, oil flowline, leaks.